2016
DOI: 10.1177/0047281616646749
|View full text |Cite
|
Sign up to set email alerts
|

Improving Patient Discharge Communication

Abstract: Transitional care communication events-such as discharge from hospital-are complex and dynamic: impromptu questions are asked and answered, documents are discussed and signed, and health-care professionals and patients with different knowledge must work together to establish understanding. This article examines a set of patient discharge instructions that bear substantial traces of impromptu conversation in the patient discharge communication process and argues that we need to do more to account for such excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Researchers and theorists in composition studies and the rhetoric of health and medicine have developed research methods based on Guattari and Deleuze’s (2000) assemblage thinking (e.g., Angeli, 2018; Fox, 2002; Rice, 2008) and Latour’s (2005) actor-network theory (ANT; e.g., Kelly & Maddalena, 2016). 4 Several authors have also used Rivers and Söderlund’s (2016) concept of speculative usability, which applied ANT to usability testing and argued that researchers should consider and address all possible human and nonhuman contributors (Arduser, 2018; Cannon, Walkup, & Rea, 2016; Gouge, 2017). Others have adopted Edbauer’s (2005) concept of rhetorical ecologies to frame research on complex systems in health care (e.g., Ehrenfield, 2018; Jensen, 2015; Scott, 2006; Swarts, 2006).…”
Section: Methodologies and Methods That Inform Mhealth Communicationmentioning
confidence: 99%
“…Researchers and theorists in composition studies and the rhetoric of health and medicine have developed research methods based on Guattari and Deleuze’s (2000) assemblage thinking (e.g., Angeli, 2018; Fox, 2002; Rice, 2008) and Latour’s (2005) actor-network theory (ANT; e.g., Kelly & Maddalena, 2016). 4 Several authors have also used Rivers and Söderlund’s (2016) concept of speculative usability, which applied ANT to usability testing and argued that researchers should consider and address all possible human and nonhuman contributors (Arduser, 2018; Cannon, Walkup, & Rea, 2016; Gouge, 2017). Others have adopted Edbauer’s (2005) concept of rhetorical ecologies to frame research on complex systems in health care (e.g., Ehrenfield, 2018; Jensen, 2015; Scott, 2006; Swarts, 2006).…”
Section: Methodologies and Methods That Inform Mhealth Communicationmentioning
confidence: 99%
“…Relatedly, research within medicine, medical informatics, and medical internet research frequently involves patients in usability testing or UX analyses, particularly when evaluating digital health interventions, and aligns with participatory design and PXD, in that usability testing often takes place mid-development of a digital tool, and incorporates both usability testing and elements of user-experience data collection as part of enacting a user-centered design (e.g., see Beatty et al, 2018;Hong et al, 2014;Mayberry et al, 2016). However, the goal often driving these studies is to develop a tool that encourages patient compliance with a digital intervention (e.g., see Baldwin et al, 2017), a goal that has been compellingly critiqued within and beyond rhetoric and TC (see Gouge, 2017). While incorporating participatory design principles and patients as participants are steps toward PXD, usability research in medical disciplines could benefit from PXD's attunement to the highly contextualized and complex nature of patient experience.…”
Section: Critiques Of Traditional Usability and The Emergence Of Pxd In Technical Communicationmentioning
confidence: 99%
“…This was enabled by our multidisciplinary collaboration between a usability research team and a medical research team. Based on this collaborative experience, we advance PXD as a methodology and also complicate claims that "standard usability methods (e.g., think-aloud protocols, card sorting) are not sufficiently developed to work in health care contexts" (see also, Gouge, 2017;Melonçon, 2017, p. 21). We observed that think-aloud protocols and open-ended, post-task questions included in traditional usability tests elicited valuable patient experience data.…”
Section: Critiques Of Traditional Usability and The Emergence Of Pxd In Technical Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…These example situations increasingly represent today's healthcare context where individuals use technologies to perform healthcare activities on themselves or a loved one (Gittel, 2009;Gouge, 2016;Woods, 2019). For these reasons, technical communicator need to become involved in creating health and medical materials to address audience usability expectations and avoid assumptions that could affect usability.…”
Section: Scripts Disconnects and Usability Issues In Contexts Of Carementioning
confidence: 99%